Advances in Multimodal Imaging Techniques for Evaluating and Predicting the Efficacy of Immunotherapy for NSCLC - Liu J; Xie M; Shen J; Yao J; Lin X; Bao X; Zhang X; Liang Y; Yang Y; Jiang G; Diao X; Han W; et al. (Cancer Management and Research)
Jingyi Liu,1 Mei Xie,2 Jing Shen,1 Jie Yao,2 Xuwen Lin,2 Xinyu Bao,3 Xin Zhang,3 Yiran Liang,2 Yun Yang,1 Gege Jiang,1 Ximeng Diao,1 Wenya Han,4 Hai Du,5 Xinying Xue,3,6 Jianlin Wu1 1Department of Radiology, Affiliated Zhongshan Hospital of Dalian University, Dalian, 116001, People’s Republic of China; 2Department of Respiratory and Critical Care, Emergency and Critical Care Medical Center, Beijing Shijitan Hospital, Capital Medical University, Beijing, 100038, People’s Republic of China; 3Department of Respiratory and Critical Care, Affiliated Hospital of Shandong Second Medical University, Weifang, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, Taihe Hospital, Hubei University of Medicine, Shiyan, 442000, People’s Republic of China; 5Ordos Central Hospital, Ordos City, 017000, People’s Republic of China; 6Department of Respiratory and Critical Care, Xuanwu Hospital, Capital Medical University, Beijing, 100038, People’s Republic of ChinaCorrespondence: Jianlin Wu, Department of Radiology, Affiliated Zhongshan Hospital of Dalian University, Dalian, 116001, People’s Republic of China, Email cjr.wujianlin@vip.163.com Xinying Xue, Department of Respiratory and Critical Care, Xuanwu Hospital, Capital Medical University, Beijing, 100038, People’s Republic of China, Email xuexinying2988@bjsjth.cnAbstract: Immunotherapy has emerged as a transformative treatment for non-small cell lung cancer (NSCLC), yet its clinical benefits remain variable among patients. Early and accurate evaluation of treatment response is critical to guide therapeutic adjustments and improve outcomes. This review synthesizes recent advancements in multimodal imaging techniques—computed tomography (CT), positron emission tomography (PET)/CT, magnetic resonance imaging (MRI), and radiomics—for evaluating and predicting immunotherapy efficacy in NSCLC. We analyze the strengths and limitations of conventional morphological criteria (eg, RECIST, iRECIST) and highlight emerging quantitative biomarkers, including CT texture analysis, metabolic parameters (MTV, TLG), and diffusion-weighted MRI metrics. Notably, radiomics demonstrates promise in decoding tumor heterogeneity, PD-L1 expression, and immune microenvironment features, while immuno-PET probes targeting immune checkpoints offer novel insights into immune activity in vivo. Challenges such as pseudo-progression, nodal immune flare, and discrepancies between imaging responses and pathological responses are critically discussed. By integrating morphological, metabolic, and microenvironmental data, multimodal imaging enhances precision in patient stratification and therapeutic monitoring. Future research should prioritize multicenter, AI-driven radiomics validation and targeted tracer development to optimize NSCLC immunotherapy management. This review provides clinicians and researchers with new directions for utilizing multimodal imaging techniques in developing personalized treatment strategies.Keywords: non-small cell lung cancer, immunotherapy, efficacy prediction, CT, PET, MRI